The cognitive neuroscience of lucid dreaming - Baird, Benjamin; Mota-Rolim, Sergio A.; Dresler, Martin (Neuroscience and biobehavioral reviews, 2019)
•EEG studies of lucid dreaming are mostly underpowered and show mixed results.•Preliminary neuroimaging data implicates frontoparietal cortices in lucid dreaming.•Cholinergic stimulation with mental set shows promise for inducing lucid dreams.•We present best-practice procedures to investigate lucid dreaming in the laboratory. Lucid dreaming refers to the phenomenon of becoming aware of the fact that one is dreaming during ongoing sleep. Despite having been physiologically validated for decades, the neurobiology of lucid dreaming is still incompletely characterized. Here we review the neuroscientific literature on lucid dreaming, including electroencephalographic, neuroimaging, brain lesion, pharmacological and brain stimulation studies. Electroencephalographic studies of lucid dreaming are mostly underpowered and show mixed results. Neuroimaging data is scant but preliminary results suggest that prefrontal and parietal regions are involved in lucid dreaming. A focus of research is also to develop methods to induce lucid dreams. Combining training in mental set with cholinergic stimulation has shown promising results, while it remains unclear whether electrical brain stimulation could be used to induce lucid dreams. Finally, we discuss strategies to measure lucid dreaming, including best-practice procedures for the sleep laboratory. Lucid dreaming has clinical and scientific applications, and shows emerging potential as a methodology in the cognitive neuroscience of consciousness. Further research with larger sample sizes and refined methodology is needed.